The Successful Use of a Novel Microwave Device in the Treatment of a Plantar Wart - Ivan Robert Bristow; Christopher Webb; Michael Roger Ardern-Jones (Karger Publishers, 2017)
Plantar warts, caused by the human papilloma virus (HPV), are a commonly encountered condition presenting in clinic. In adults, an array of various therapies exists, frequently with modest results particularly with plantar lesions. Microwaves have had limited uses for medical purposes. Recently a new portable microwave device has been approved for the treatment of skin lesions. Prior research has demonstrated immuno-stimulatory effects against HPV infection. We report the application of a novel portable medical microwave unit to treat a long-standing plantar wart which had failed to respond to other treatment modalities.